In Silico, to Determine The Active Compounds of Black Tea and Turmeric In Increasing The Activity of The Enzyme Sod - Akhmad Endang Zainal Hasan; Mega Safithri; Aziz Syamsul Huda; Rini Kurniasih (Indonesian Journal of Applied Research (IJAR), 2022)
Damage to cells caused by stress can be reduced by the presence of antioxidants, one of which is Superoxide dismutase (SOD). The role of the active ingredients of black tea and turmeric will be studied using the in-silico method to identify the active compounds as components in SOD activation. The bioavailability and toxicity of the active compounds of black tea and turmeric were studied and followed by molecular docking and virtual games. The parameters studied are Gibbs's free energy (∆G) and binding site similarity (BSS). The results were analyzed using Gibbs's free energy (∆G) and binding site similarity (BSS) parameters. It was found that those that could increase the activity of Cu/Zn SOD enzymes were Epicatechin gallate (black tea) and curcumin (turmeric), with values ​​of -9.5 and -7.4 Kcal/mol and the same BSS value of 81.8%. The control ligand used was beta amyrin. According to Lipinski's rules, Epicatechin gallate and curcumin compounds can be absorbed well and are safe for consumption. This study concludes that Epicatechin gallate, an active compound of black tea, and curcumin, an active compound of turmeric rhizome, have the best potential to increase the activity of Cu/Zn SOD enzymes based on the results of virtual screening and molecular docking. Epicatechin gallate and curcumin are predicted to be well absorbed by the body because they qualify Lipinski's rules and are not toxic and safe for consumption.